PELATIHAN PENULISAN ARTIKEL ILMIAH BERBANTUKAN MANAJEMEN REFERENSI MENDELEY - Sulfaidah; Al Banna, Maisya Zahra; Sapinah; Liana, Alin (Jurnal Berdaya Mandiri, 2023)
The publication is the first step for transferring the results of thoughts and research widely to the public. Writing the effects of studies and research is required as a condition for the acceptance of scientific articles by a scientific journal. This training was purposed to improve the ability of teachers to produce scientific papers and practice skills in using Mendeley reference management in managing libraries. This research method includes survey, pretest, training implementation, practicum, and posttest. The workshop activity was carried out through WhatsApp Group, followed by 13 participants who followed the training until the end. The data from the pretest and posttest were analyzed using the Gain score method. The workshop results showed that the knowledge and skills of the participants increased by an average of 2,231 points. Another indicator is known from the ability of participants to apply Mendeley reference management in scientific articles. Currently, four participants have successfully published scientific papers in national journals. This training is considered beneficial and can improve the knowledge and skills of teachers in writing scientific articles with the help of Mendeley reference management. Key Word: Scientific paper; Teacher; Mendeley; Publication; Universitas Patompo